Ulnar Impaction Syndrome: Ulnar Shortening vs. Arthroscopic Wafer Procedure - De Smet, Luc; Vandenberghe, Lore; Degreef, Ilse (Journal of Wrist Surgery, 2014)
The outcome of ulnar shortenings was compared with that of arthroscopic wafer resections for ulnar impaction (or abutment) syndrome in patients with a positive ulnar variance. The outcome was measured by DASH score, visual analog scale for pain, and working incapacity. The mean DASH score in the ulnar shortening group was 26; in the wafer group it was 36. The VAS scores were respectively 4.4 and 4.6. The working incapacity was 7?months in the ulnar shortening group and 6.1 months in the wafer group. The differences between the two groups were not statistically significant.
Keywords: ulnar impaction; shortening osteotomy; arthoscopy; TFCC; wafer